Implementation of the Food Strengthening Policy in the Agricultural Sector by the Agriculture Office of North Maluku Province in the Jailolo Sub-District - Muhtar Husen (Edunity Kajian Ilmu Sosial dan Pendidikan, 2023)
This study aims to analyze the implementation of food-strengthening policies by the North Maluku Provincial Agriculture Office in Jailolo District. The research method used is qualitative with a case study approach. Data was collected through in-depth interviews with farmers, Department of Agriculture staff, and local community leaders. Data analysis is carried out using content analysis techniques. Research findings show that the implementation of food-strengthening policies in the Jailolo sub-district faces various challenges, including limited human and financial resources. Despite this, some measures have been taken to increase agricultural productivity and food availability. Recommendations are prepared to improve the effectiveness of policy implementation, including improved coordination among stakeholders and adequate budget allocation. This research is expected to contribute to the improvement of agricultural policies and practices at the local and regional levels